The Role of Balanced Scorecard Technology in Evaluating Sustainable Performance - Mahdi Al Julokhan, Zainab; Mahdi Al Kawaz, Salah (Iraqi Journal for Administrative Sciences, 2025)
The research aimed to identify the philosophy of the balanced scorecard and to contribution to assessing sustainable performance, as well as to study and analyze the reality of the application of the economic units of the balanced scorecard evaluating sustainable performance. The Iraqi industrial sector was targeted, represented by the Iraqi industrial economic units specialized in the manufacture of lime, due to the importance of this sector in the field of economic development of the country, in addition to its impact on human health and the surrounding environment through industrial waste that some economic units release into the environment in its various forms and elements, and the lime factory - Karbala was chosen as the subject of the research. The research reached the most important conclusion between the application of the balanced scorecard (BSC) in the laboratory and its effectiveness in evaluating sustainable performance through the results that showed an improvement in sustainable performance in general. In 2021, the result was (58%) and in 2023 it became (60%).